THE EFFECT OF FRESH TEA WASTE FERTILISER (NON-COMPOST) ON MINT PLANTS GROWTH - Razali, Farah Najihah; Kamaruzaman, Nur Fatin Ayuni (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Mint plant is widely used in cooking and also medicinal use. Hence, ability to increase their production will meet the demand of mint plant in the market. There are various of organic fertilisers available and one of them is tea waste fertiliser. However, majority of the waste fertiliser used in studies were the composted one. This study highlights the effect of fresh tea waste (non-composted) on the growth of mint plant (number of leaves and number of branch and the w of this study is to determine the optimum concentration of fresh tea waste fertiliser on the growth of three groups of mint plant (T0, T1 and T2) in a period of 8 weeks. T0 is the control group, whereas T1 and T2 were supplemented with fertiliser at different concentration. Soil pH measures were taken to study if fertilisers had brought any effect on the plant soil pH. The results showed that there were significantly change in plant growth between the group of studies, rather it affects negatively. Both T1 and T2 showed a noticeable reduction in number of leaves and branches. Fresh tea waste supplies organic nitrogen and micronutrients and can increase soil organic matter however, it contains tannins and polyphenols that can be phytotoxic at high level. This explains the negative results shown in this study. Even though some studies recorded the drop in soil pH as tea can acidify the soil, however this study recorded that some fluctuation in soil pH but it rather insignificant. In short, we see some potential of fresh tea waste as an eco-innovative fertiliser that can support plant growth but some modification of the formulation of the fertiliser is needed in order to produce the positive results.